2021
DOI: 10.1155/2021/6661109
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax Combined with Hypomethylating Agents for Treatment-Naïve B/Myeloid Mixed Phenotype Acute Leukemia

Abstract: Mixed phenotype acute leukemia (MPAL) is a rare hematological malignancy that lacks consensus on optimal management. We report for the first time two cases of treatment-naïve B/myeloid MPAL patients treated with a novel chemo-free regimen using venetoclax combined with hypomethylating agents, which successfully induced complete remission with tolerable toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In one study, two treatment-naïve patients were treated with a combination of a hypomethylating agent and the B-cell lymphoma-2 (BCL-2) inhibitor, venetoclax. Both patients subsequently received ASCT after achieving CR [ 15 ]. Additionally, blinatumomab, a bi-specific T-cell engager (BiTE) monoclonal antibody directed against CD19 was used to treat a patient whose performance status declined while being treated with hyper-CVAD.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, two treatment-naïve patients were treated with a combination of a hypomethylating agent and the B-cell lymphoma-2 (BCL-2) inhibitor, venetoclax. Both patients subsequently received ASCT after achieving CR [ 15 ]. Additionally, blinatumomab, a bi-specific T-cell engager (BiTE) monoclonal antibody directed against CD19 was used to treat a patient whose performance status declined while being treated with hyper-CVAD.…”
Section: Discussionmentioning
confidence: 99%
“…Klocke et al [ 32 ] reported the case of a 65-year-old man with a complicated story of recurring relapses, ultimately controlled by the administration of venetoclax and decitabine, allowing to perform a second Allo-HSCT that led to more than 1 year of sustained CR at the time of publication. Finally, two patients with bi-lineal MPAL successfully received Allo-HSCT after chemotherapy lines of treatment including venetoclax and remain in CR several months later [ 33 ].…”
Section: Treatment Of Mpalmentioning
confidence: 99%
“…Pre-clinical and clinical research has been conducted in KMT2A -rearranged leukemia (particularly in infants) and has shown increased sensitivity to both FLT3 and RAS inhibition, which could be translated into MPAL patients harboring such mutations [ 67 , 68 , 69 ]. Novel agents such as BCL-2 inhibitor venetoclax, in combination with hypomethylating agents, have been used to induce remission in MPAL [ 70 , 71 , 72 ]. Given the unique biology of MPAL, engineering hematopoietic stem cells harboring altered transcription factor profiles could mimic a pre-clinical model and allow the expanded testing of novel target agents, using a precision-medicine approach.…”
Section: Novel Approachesmentioning
confidence: 99%